"It's the last resort'' forensic mental health nurses experience on the use of seclusion; implications for use and elimination in clinical practice. Issue 6 (2nd November 2022) - Tulloch, Lindsay; Walker, Helen; Ion, Robin
ABSTRACT: Seclusion is one of the extreme measures of managing violence and aggression. Despite the evidence base for the effectiveness and therapeutic value of seclusion being limited, there arguably remains a compelling case for its use. This qualitative study aimed to explore forensic nurse's experiences and perspective on the use of seclusion in clinical practice and establish: What are the factors that influence and inhibit the use of seclusion? What skills are required when caring for patients in seclusion? A purposive sample of 12 registered and non-registered nurses from a UK high-security hospital consented to engage in a focus group. Thematic analysis was used to interrogate the data. The results included two emerging themes: 'Keeping everyone safe' and 'The challenges', including the identification of binary oppositions. A rationale for the use of seclusion; it's a last resort. Evidence of challenges to the therapeutic relationship and communication barriers. Findings illustrate the need to critically examine the practise of seclusion, accuracy of risk assessment, also to balance safety and security proportionately and ensure therapeutic value. The use of a daily dynamic risk assessment and staff relational training is recommended to improve communication and reduce excessive and prolonged use of seclusion Summary: What is known on the subject Over the last decade, significant headway has been made across the globe in relation to reducing restrictive practices such as seclusion. Early intervention and staff confidence in managing violence and aggression have been identified as factors that influence the occurrence of seclusion. What the paper adds to the existing knowledge Findings support the necessity to utilise objective assessment routinely. The binary oppositions described within the presenting results are as relevant today as they were almost two decades ago when published by Mason (2002 ) This paper provides new knowledge on forensic nurses' perception use of seclusion and draws attention specifically to the impact of the therapeutic relationship and communication challenges during a seclusion event. What are the implications for practice The provision of a daily dynamic risk assessment within nursing practice will effectively identify patients who are imminently at risk of engaging in violence and aggression and reducing excessive and/or prolonged use of seclusion. Staff development and development that includes relational skills training in how to manage complex relationships to improve positive communication and reduce the need for seclusion being required. The findings suggest the need for future research and senior managers and health-care professional leaders to gain a better understanding of the factors that influence the clinicians' decisions in the use seclusion, in order to achieve long-term reductions in its use.